The effect of pictorial mode on children’s learning of new L1 lexical items - Firooz Sadighi; Sepideh Nourinezhad (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2018)
This research is aimed at investiagting the influence of using pictorial mode towards children’s learning of L1 new lexical items. This study is based on an experimental design. To reach the goal, 20 children as the sample were randomly selected from nurseries in Shiraz, Iran. The participants were 3 years old children divided in two groups of experimental and control. To estimate the impact of pictorial mode on children’s learning of L1 new lexical items, the same lexical items (the name of 3 animals) were provided to each group with different media; flashcard used in the experimental group, and in the control group just used some explanations about the characteristics of the animals. To collect the data, the researchers recorded children’s voice and then transcribed and scored their answers. The data were then analyzed using independent-samples t-test. The result shows that inasmuch as those in the experimental group surpassed those in the control group, it came to light that the use of pictorial mode greatly influenced children’s learning of new L1 lexical items.